Innovation and performance on manufacturing companies in Kota Kinabalu, Sabah - Ang, Hong Loong (2015)
The purpose of this study is to examine the relationship between innovation, innovative and production performance amongst manufacturing companies in Kata Kinabalu with the moderating effect of year of establishment. In this study, innovative is conceptualized as a multidimensional construct which consist four dimensions of innovation (i.e. product innovation, process innovation, marketing innovation and organizational innovation). Managerial level employees whom are qualified to represent their manufacturing companies in making decisions are the participants in this study. Data from 323 respondents were used for the statistical analysis using Partial Least Squares Structural Equation Modeling. The data were collected using the disproportionate stratified random sampling approach. measurement model, structural model and moderator analysis were employed to test the relationships between innovation, innovative performance and production performance with the moderating effect of year of establishment. The results showed that innovation are related to product innovation, process innovation and organizational innovation have a significant influence on innovative performance. In addition, there is evidence that innovation related to product innovation, process innovation and organizational innovation also have a significant effect on production performance. However, marketing innovation does not have a significant relationship with innovative performance and the relationship between marketing innovation and production performance is not supported. Furthermore, the year of establishment of organization moderates the relationship between innovation and innovative performance. Also, this year of establishment moderates the relationship between innovation and production performance. Specifically, this study found that the moderating role of year of establishment with a high year of establishment (11 years and above) has a positive relationship between organizational innovation and innovative performance, whereas low year of innovation and production performance. The results imply that manufacturing., performance and production performance.